2015
DOI: 10.1097/sa.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Versus On-Pump Coronary-Artery Bypass Grafting in Elderly Patients

Abstract: T he benefits of coronary artery bypass grafting (CABG) without cardiopulmonary bypass in the elderly has yet to be determined. Patients 75 years or older who were scheduled for elective first-time CABG were randomly assigned to undergo the procedure either without cardiopulmonary bypass (off-pump CABG) or with it (on-pump CABG). The primary end point was a composite of death, stroke, myocardial infarction, repeat revascularization, or new renal replacement therapy at 30 days and 12 months after surgery. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 2 publications
0
61
0
7
Order By: Relevance
“…Additionally, other observational studies suggested that high-risk patients, such as patients with cerebrovascular atherosclerosis, severe atherosclerotic aorta or peripheral arterial disease, showed a significant reduction in stroke incidence after OPCAB [71][72][73]. Conversely, a number of randomized studies comparing the OPCAB strategies with the conventional on-pump CABG procedures have failed to show an advantage with OPCAB regarding stroke [74][75][76]. As an example, the ROOBY trial randomly assigned 2203 patients to either on-pump or offpump procedures and found no difference between the two groups in stroke rate [76].…”
Section: Off-pump Cabgmentioning
confidence: 95%
“…Additionally, other observational studies suggested that high-risk patients, such as patients with cerebrovascular atherosclerosis, severe atherosclerotic aorta or peripheral arterial disease, showed a significant reduction in stroke incidence after OPCAB [71][72][73]. Conversely, a number of randomized studies comparing the OPCAB strategies with the conventional on-pump CABG procedures have failed to show an advantage with OPCAB regarding stroke [74][75][76]. As an example, the ROOBY trial randomly assigned 2203 patients to either on-pump or offpump procedures and found no difference between the two groups in stroke rate [76].…”
Section: Off-pump Cabgmentioning
confidence: 95%
“…Pour les troubles cognitifs é valué s à un an, une mé ta-analyse confirme l'absence de diffé rences entre les deux techniques chirurgicales [63]. De plus, même si plusieurs é tudes plaident pour cette technique chez les patients à risque chirurgical é levé et âgé s de plus de 80 ans [64][65][66][67][68], une nouvelle é tude ne montre pas de diffé rence dans ce dernier groupe pour l'incidence des AVCI et des troubles cognitifs [69]. L'inté rêt des pontages coronaires à coeur battant est donc remis en question.…”
Section: Chirurgie Cardiaqueunclassified
“…Combined with the recent outcomes of the GOPCABGE study [German Off-Pump Coronary Artery Bypass Grafting in Elderly Patients] demonstrating no difference in on-pump or off-pump CABG in elderly patients, much of the large, contemporary literature on off-pump CABG indicates that, unlike the results of the ROOBY [Randomized On/Off Bypass] trial, off-pump is at least noninferior to on-pump CABG [1,2].In this growing era of comparative effectiveness research, however, we see a trend toward assessing new technologies not only with regard to their clinical effectiveness but also cost effectiveness [3]. Thus, while onpump and off-pump techniques appear to have similar clinical outcomes, could one technique prove more effective through lower overall costs?…”
mentioning
confidence: 93%
“…Combined with the recent outcomes of the GOPCABGE study [German Off-Pump Coronary Artery Bypass Grafting in Elderly Patients] demonstrating no difference in on-pump or off-pump CABG in elderly patients, much of the large, contemporary literature on off-pump CABG indicates that, unlike the results of the ROOBY [Randomized On/Off Bypass] trial, off-pump is at least noninferior to on-pump CABG [1,2].…”
mentioning
confidence: 95%